å¤ç”¸åœ£çˆ¶åˆä¸å¦æ ¡äºŒå¹´çº§çš„å¦ç”Ÿä½¿ç”¨æ±‰è¯åé‡è¯â€œåªâ€ã€â€œå¤´â€ã€â€œæ¡â€çš„ åè¯¯åˆ†æž - TANI, AMBOROSIA (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstractâ€œPronounsâ€ are one of the auxiliaries often used in learning Mandarin. For instance, the pronouns of â€œzhiâ€, â€œtouâ€, and â€œtiaoâ€ are often applied in daily conversation. There are some similarities and slight differences among those pronouns so the students often found it hard in the usage. The research of the application of â€œzhiâ€, â€œtouâ€, and â€œtiaoâ€ pronouns was conducted to the 8th grade students in SMP Bruder Pontianak. From the data collection, the writer may concluded that 42%, 49% and 50% in percentage where as the 8th grade students of SMP Bruder Pontianak made mistakes in the usage of the pronouns of â€œzhiâ€,â€œtouâ€, and â€œtiaoâ€. Most of the mistakes are in structure order. It was because most of the students had not been taught specifically about the usage of the three pronouns and they still found it difficult in understanding the questions. Based on the findings, the writer would like to propose some constructive suggestions to these three pronouns. Keywords: the pronouns of â€œzhiâ€, â€œtouâ€, and â€œtiaoâ€ Error Analysis Â